Transnational Crime of Cross-Border Narcotics Smuggling between Riau and Malaysia - Muhammad Zulherawan; Mohamad Fauzi Latib; Salma Andina (Journal of Multidisciplinary Law Studies, 2026)
Transnational crime refers to criminal activities that involve multiple actors and span across more than one country. Such crimes violate the legal regulations and territorial jurisdictions of each affected state. One of the most common forms of transnational crime occurring within the jurisdiction of the National Narcotics Agency of the Riau Islands Province (BNNP Kepulauan Riau) is drug smuggling. This drug smuggling is driven by various factors, one of which is the geographical location and condition of Batam City, which consists of numerous small islands and several ports that facilitate smuggling activities. This study aims to analyze the causal factors, operational patterns, and criminological characteristics of transnational narcotics smuggling activities occurring between Riau Islands and Malaysia. The study applies subjective utility (rational choice) theory to explain how offenders rationally evaluate economic benefits, operational risks, and opportunities for successful smuggling before engaging in transnational narcotics trafficking. The findings reveal that economic incentives, weak maritime supervision, and the strategic geographical position of Batam significantly encourage organized transnational narcotics smuggling networks, thereby reinforcing the importance of integrated cross-border law enforcement and maritime surveillance policies.